Income inequality - Eboch, M. M. (Introducing issues with opposing viewpoints., 2022)
Presents sixteen opposing essays on income inequality. Discusses its causes and effects, and how it can be reduced. Includes color photographs, charts and graphs, fact boxes, sidebars, statistics, critical thinking questions, organizations to contact, and further resources.